SEISMIC ANALYSIS USING STRENGTH BASED DESIGN METHOD AND PERFORMANCE BASED DESIGN METHOD: STUDY CASE OF PURI AZIZI PURI HOSPITAL ON MEDAN, NORTH SUMATRA - Yulina Anastesi Simbolon; Chunyang Zhu (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2025)
The seismic analysis employing the Strength Based Design (SBD) technique follows the standards specified in SNI 1726:2019, whereas the technic of Performance Based Design (PBD) method adheres based on regulations outlined in ATC 40.The seismic analysis data is acquired from the contractor such as shop drawing. Prior to conducting the analysis, the modeling willbe performed initially using SAP 2000. The Strength Based Design (SBD) technique involves conducting linear elastic analysisaccording to conventional seismic design standards outlined in SNI 1726:2019. These standards prioritize the strength of materialsand structural elements. Meanwhile, the Performance Based Design (PBD) involved conducting a Static Nonlinear PushoverAnalysis Procedure B. This analysis considers the degree of performance and structural behavior under different earthquakesituations, utilizing performance criteria stated in international standards. In Strength Based Design (SBD), the base shear (V)value obtained is 497551.96 kgf. In Performance Based Design (PBD), the base shear (V) value obtained is 623230.3 kgf. Thepushover study using procedure B yielded a Sa value of 0.095 and a sd value of 0.023. According to the specifications of ATC-40,the performance level of the structure is found to be in the Immediate Occupancy phase. This conclusion is based on the deformation of the structure. The greatest total drift that is allowed for building structures is the phase that corresponds to this phase.